Occurrence of Comorbidities before and after Soft Tissue Sarcoma Diagnosis. (28th May 2012) - Herk-Sukel, Myrthe P. P. van; Shantakumar, Sumitra; Overbeek, Lucy I. H.; van Boven, Hester; Penning-van Beest, Fernie J. A.; Herings, Ron M. C.
Abstract : Background . Data is limited on the burden of common comorbidities, such as cardiovascular disease (CVD), respiratory disease and diabetes, or comorbidities related to cancer and its treatment, such as anemia and depression, in patients with soft tissue sarcoma (STS). Patients and Methods . From the Dutch Pathology Registry linked to the PHARMO database (including data on drug use and hospitalizations), 533 patients with STS were selected during 2000–2007 and matched 1 : 10 to cancer-free controls. The occurrences of comorbidities were assessed in the 12 months before and after STS diagnosis. Results . STS patients were 2–4 times more likely to have comorbidities at diagnosis compared with cancer-free controls. The incidence of CVD, anemia, and depression after STS diagnosis differed significantly from cancer-free controls and decreased during followup from 40–124 per 1, 000 person-years (py) during the first six months to 11–38 per 1, 000 py more than 12 months after diagnosis. The incidence of respiratory disease and diabetes among STS patients remained stable during followup (5–21 per 1, 000 py) and did not differ significantly from cancer-free controls. Conclusions . STS patients were more likely to have comorbidities before cancer diagnosis and to develop CVD, anemia, and depression after diagnosis compared to cancer-free controls.